Effects of Land use Change on Dung Beetle (Scarabaeinae) Community Structure in South Western Ghats - Latha, Thomas; K. Sabu, Thomas (International Journal of Environment, Agriculture and Biotechnology, 2019)
Western Ghats in the Indian subcontinent is one of the world’s eight ‘hottest hotspots’ of biological diversity along with Sri Lanka. Land use changes in the Western Ghats caused by agricultural expansion and other anthropogenic activities have resulted in loss of forests and is a major threat to Western Ghats biodiversity. In the present study, Scarabaeinae dung beetles were used as biological indicators to study the effects of land use change on biodiversity in the South Western Ghats. Community attributes such as abundance, species richness, species composition, functional guild composition, temporal guild composition and beetle sizes were compared between a forest and agriculture habitat in the South Western Ghats region. Cow dung baited pitfall traps were used to collect dung beetles in the presummer, summer and monsoon season during 2007-2008 study period. The study showed that dung beetle community attributes were affected due to land use changes. Of the 31 species collected between the two habitats, only 15 species were shared between forest and agriculture habitat accounting for 51.6% species turnover. Low abundance recorded in agriculture habitat resulted from low diversity and amount of dung types available to beetles when compared to forest habitat, while high species richness in agriculture habitat resulted from the presence of heliophiles and synanthropic species that has established in the region owing to decades of anthropogenic disturbance. Functional guild tunneler, dominated both the habitats because of their superior competitive nature. Temporal guild was dominated by nocturnal guild in the forest due to the availability of dung at night from wild animals, and diurnal guild in agriculture habitat owing to the availability of dung during the day as a consequence of agricultural practices. Small beetles dominated both the habitats as a result of decline in large dung pad producing mammals in the region as a consequence of anthropogenic disturbance. Further deterioration of forests in the region is important to conserve the remaining forest specialists.